Effect of Self-Care Training Based On VARK Learning Style Preference on Blood Pressure of Patients with Hypertension - Zeinab Ghorbani; Elham Imani; Saeed Hoseini Teshnizi (Golestan University of Medical Sciences, 2022)
Background: Hypertension has been a global public health crisis. Complications of hypertension can be reduced by educating patients. Consideration of the learning styles of patients is important for effective education. The aim of this study was to determine effects of self-care training based on visual, aural, reading/writing, and kinesthetic (VARK) learning style preference on blood pressure of hypertensive patients. Methods: This semi-experimental study was conducted in Bandar Abbas, South of Iran in 2019. Forty-four eligible patients who were referred to six comprehensive health centers in Bandar Abbas were selected by convenience sampling and then allocated into four visual, aural, reading/writing, and kinesthetic groups based on the results of the VARK learning style questionnaire. Educational interventions were performed according to patients' learning style preference in four sessions. To evaluate effectiveness of the training, patients' blood pressure was measured before the intervention and two months after the intervention. Data were analyzed with SPSS 16 software using paired t-test, Wilcoxon test, and one-way analysis. Results: After the educational intervention, a statistically significant difference was observed in the mean systolic and diastolic blood pressures of all patients (P<0.001). After the intervention, the mean systolic blood pressure did not change significantly in the kinesthetic group (P>0.05) but decreased significantly in other groups (P<0.05). In addition, the mean diastolic blood pressure decreased significantly after the intervention in all study groups (P<0.05). Conclusion: Providing education based on the preferred learning style can be an effective way to educate patients with hypertension in comprehensive health care centers across the country.